Detection of Lassa Virus, Mali - David Safronetz; Job E. Lopez; Nafomon Sogoba; Sékou F. Traore’; Sandra J. Raffel; Elizabeth R. Fischer; Hideki Ebihara; Luis M. Branco; Robert F. Garry; Tom G. Schwan; Heinz Feldmann (Emerging Infectious Diseases, 2010)
To determine whether Lassa virus was circulating in southern Mali, we tested samples from small mammals from 3 villages, including Soromba, where in 2009 a British citizen probably contracted a lethal Lassa virus infection. We report the isolation and genetic characterization of Lassa virus from an area previously unknown for Lassa fever.